Systematic review: Factors influencing creativity in the design discipline and assessment criteria - Dai Zetian; Wee Hoe Tan; Ren Shumin; Zhang Menglin; Mansour Amini; Wang Shoushan (Institute of Advanced Engineering and Science, 2023)
Using psychological instrument to measure creativity is getting popular in design research. However, unlike quantifying general creativity using divergent thinking, the complexity and interdisciplinarity of the design discipline have made it difficult to explore research on design creativity. Therefore, to better quantify and measure design creativity, 31 relevant studies were retrieved by Google Scholar and the University of London Common Research in this article. This study summarizes the factors that influence design creativity in different design disciplines, the rules for setting the internal dimensions, and the valid instruments for measuring design creativity. The factors affecting design creativity can be divided into internal factors (aesthetic, spatial ability, and ambiguity tolerance) and external factors (environment and visual stimulation). Among these factors, different instruments and evaluation criteria considerably impact the result, while the measurement of design creativity is still not mature enough. A single scale evaluation or creative task evaluation cannot comprehensively evaluate the design creativity, which consists of aesthetic, functional, and technical aspects. In addition, the reference value of ordinary creativity remains to be further discussed in design. Under some professional design fields, the effect of widely recognized factors closely related to creativity, such as divergent thinking, imagination, and personality, is insignificant.